The role of syntax semantics development in teaching a foreign language to future teacher-engineers - Remizantseva, E. A.; Zelenin, G. I. (Problems of Engineer-Pedagogical Education, 2018)
The scientists’ views on the essence of the problem of syntax semantics development in a language were analyzed in the article. It is revealed that the ontogenesis of speech activity is а complex process, which includes many different contradictory development lines, intersecting general psychological, mental, and cognitive development of a human. It is alleged that the scholars emphasized the importance to start the analysis of linguistic activity in any language from early childhood. Functions and types of speech activity are defined here too. It is noted that the statements can be regarded as a special kind of sign, which is the main feature of communication. It means that the speech signs act as a connecting link between the objective world and the people’s consciousness, their experience which is developed in the activity process. It is proved that such processes occur with future teacher-engineers at the initial stage of studying professional business foreign language. Thus, in the semantic development of the professional foreign language syntax, students go through the same stages of development, as children mastering their native language, so it is important to understand how syntax semantics of human’s language develops.